Novel power battery negative plate lead paste and preparation method thereof

By using elastically enhanced conductive filler combined with modified carbon nanotubes and polyamide short fibers in the negative plate of the power battery, the problem of poor dispersion of carbon nanotubes is solved, a stable conductive network is formed, and the cycle life and service performance of the battery are improved. .

CN119275283APending Publication Date: 2025-01-07TIANNENG GRP HENAN ENERGY TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350639.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The dispersion performance of carbon nanotubes in the negative plate of existing power batteries is poor, resulting in unstable conductive networks and affecting the battery's service performance and life.

Method used

A new type of power battery negative plate lead paste, including lead powder, dilute sulfuric acid, elastically enhanced conductive filler (prepared by combining multi-wall carbon nanotube modified polyurethane with polyamide staple fiber) and surfactants, and dispensed through specific groups. The ratio and preparation method is used to form a stable conductive network.

Benefits of technology

It improves the mechanical strength and deformation resistance of the electrode plate, enhances the dispersion and distribution of carbon nanotubes, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a novel power battery negative plate lead plaster and a preparation method thereof, and belongs to the technical field of battery panels and preparation, and the novel power battery negative plate lead plaster comprises the following components in parts by weight: 100 parts of lead powder, 14-16 parts of dilute sulfuric acid, 4-6 parts of water, 0.38-0.42 part of an elastic enhanced conductive filler, 0.20-0.30 part of barium sulfate, 0.12-0.18 part of a surfactant, 0.10-0.14 part of humic acid and 0.05-0.07 part of sodium carboxymethyl cellulose. The prepared power battery negative electrode lead paste overcomes the problems that in the prior art, the bonding strength of pole plate active substances is poor, and a conductive network is not perfect and stable enough, and the cycle service life of a lead storage battery is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery plates and preparation thereof, and in particular to a novel lead paste for negative electrode plates of power batteries and a preparation method thereof. Background Art

[0002] When preparing negative plates for power batteries, the type and amount of carbon material in the negative electrode lead paste play a key role in the performance of the battery. The addition of carbon material can reduce the contact internal resistance between the negative plate materials and improve the charge and discharge performance of the battery.

[0003] The commonly used carbon material at present is carbon nanotubes, which have a large aspect ratio and good conductivity. However, their dispersion performance is poor and they are easy to aggregate, making it difficult to form a uniform and stable conductive system. During long-term use, the conductive network is easily damaged, affecting the performance of the battery. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the present invention provides a novel lead paste for negative plates of power batteries and a preparation method thereof.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 14 to 16 parts of dilute sulfuric acid, 4 to 6 parts of water, 0.38 to 0.42 parts of elasticity-enhanced conductive filler, 0.20 to 0.30 parts of barium sulfate, 0.12 to 0.18 parts of surfactant, 0.10 to 0.14 parts of humic acid and 0.05 to 0.07 parts of sodium carboxymethyl cellulose.

[0009] Furthermore, the preparation method of the elastic enhanced conductive filler comprises the following steps:

[0010] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes is weighed, added to 20-40 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 2.5-3.5 hours, refluxed in a constant temperature oil bath at 130-145°C, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid is 98%, and the mass fraction of concentrated nitric acid is 70%;

[0011] S2: adding the pre-oxidized carbon nanotubes prepared in S1 to 40-60 parts of N,N-dimethylformamide solvent, ultrasonically dispersing for 10-15 minutes, then adding 0.2-0.4 parts of polyacryl chloride, stirring for 5-7 hours, filtering, washing, and drying to obtain pretreated carbon nanotubes;

[0012] S3: adding the pretreated carbon nanotubes prepared in S2 to 4-6 parts of 1,4-dioxane by weight, ultrasonically dispersing for 5-10 minutes, adding 18-22 parts of hydroxyl-terminated polyurethane, adding 0.3-0.5 parts of triethylamine, and reacting for 5-8 hours to obtain carbon nanotube-modified polyurethane;

[0013] S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 2 to 4 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:95 to 105, and the length of the polyamide short fibers is 1 to 3 mm.

[0014] Furthermore, the polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer.

[0015] Furthermore, the surfactant is sodium dodecylbenzene sulfonate and / or sodium lignin sulfonate.

[0016] Furthermore, the density of the dilute sulfuric acid is 1.25 to 1.35 g / cm 3 .

[0017] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0018] A1: Mechanically premix barium sulfate, surfactant and half amount of lead powder, add dilute sulfuric acid after mixing, and stir for 20-40 minutes to obtain a premixed slurry;

[0019] A2: Heat the premixed slurry of A1 to 45-55°C, add all the remaining components except lead powder into the slurry, and stir for 1.5-2.5 hours to obtain a mixed slurry;

[0020] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0021] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0022] 1. Polyamide short fibers have high mechanical strength and are commonly used as filling materials for electrode plates. In this solution, polyurethane is pre-coated on polyamide short fibers to protect them, greatly reducing the corrosion effect of acidic media on them. At the same time, since polyurethane has high elasticity, the combination of the two has high mechanical strength and deformation resistance, which can reduce the effect of expansion and contraction of the electrode plates on the bonding strength between materials during charging and discharging, and solve the problem of stability of the electrode interface structure.

[0023] 2. The technical solution of the present invention uses carbon nanotubes to graft and enhance polyurethane, which solves the dispersion problem of carbon nanotubes. At the same time, by combining carbon nanotube-modified polyurethane with polyamide short fibers, the mechanical strength of polyamide short fibers can be further enhanced. In addition, carbon nanotube-modified polyurethane uses polyamide short fibers as a matrix. The dispersion and large specific surface area of ​​short fibers can improve the distribution problem of carbon nanotubes. The carbon nanotube-modified polyurethane and polyamide short fibers work together to ensure that the carbon nanotubes form a complete and stable conductive network, greatly improving the battery's electrical cycle performance and service life.

[0024] 3. The technical solution of the present invention overcomes the problems of poor bonding strength of active materials on the plate and imperfect and unstable conductive network in the prior art by adding specific additives to the negative electrode lead paste and optimizing the ratio between the components, thereby greatly improving the cycle life of the lead-acid battery. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 15 parts of dilute sulfuric acid, 5 parts of water, 0.40 parts of elasticity-enhanced conductive filler, 0.25 parts of barium sulfate, 0.16 parts of surfactant, 0.12 parts of humic acid and 0.06 parts of sodium carboxymethyl cellulose.

[0028] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0029] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 30 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0030] S2: adding the pre-oxidized carbon nanotubes prepared in S1 to 50 parts of N,N-dimethylformamide solvent, ultrasonically dispersing for 10 minutes, then adding 0.3 parts of polyacryloyl chloride, stirring for 6 hours, filtering, washing, and drying to obtain pretreated carbon nanotubes, wherein the polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0031] S3: adding the pretreated carbon nanotubes prepared in S2 to 5 parts of 1,4-dioxane by weight, ultrasonically dispersing for 7 minutes, adding 20 parts of hydroxyl-terminated polyurethane, adding 0.4 parts of triethylamine, and reacting for 6 hours to obtain carbon nanotube-modified polyurethane;

[0032] S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 3 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:100, and the length of the polyamide short fibers is 2 mm.

[0033] The surfactant is sodium lignin sulfonate.

[0034] The density of the dilute sulfuric acid is 1.30 g / cm 3 .

[0035] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0036] A1: Mechanically premix barium sulfate, sodium lignin sulfonate and half of the lead powder, add dilute sulfuric acid after mixing, and stir for 30 minutes to obtain a premixed slurry;

[0037] A2: Heat the premixed slurry of A1 to 50°C, add all the remaining components except lead powder into the slurry, and stir for 2 hours to obtain a mixed slurry;

[0038] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0039] Example 2

[0040] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 14 parts of dilute sulfuric acid, 4 parts of water, 0.38 parts of elasticity-enhanced conductive filler, 0.20 parts of barium sulfate, 0.12 parts of surfactant, 0.10 parts of humic acid and 0.05 parts of sodium carboxymethyl cellulose.

[0041] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0042] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 20 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 2.5 hours, refluxed in a 130°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0043] S2: adding the pre-oxidized carbon nanotubes prepared in S1 to 40 parts of N,N-dimethylformamide solvent, ultrasonically dispersing for 10 minutes, then adding 0.2 parts of polyacryloyl chloride, stirring for 5 hours, filtering, washing, and drying to obtain pretreated carbon nanotubes, wherein the polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0044] S3: adding the pretreated carbon nanotubes prepared in S2 to 4 parts of 1,4-dioxane by weight, ultrasonically dispersing for 5 minutes, adding 18 parts of hydroxyl-terminated polyurethane, adding 0.3 parts of triethylamine, and reacting for 5 hours to obtain carbon nanotube-modified polyurethane;

[0045] S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 2 h. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:95, and the length of the polyamide short fibers is 1 mm.

[0046] The surfactant is sodium dodecylbenzene sulfonate.

[0047] The density of the dilute sulfuric acid is 1.25 g / cm 3 .

[0048] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0049] A1: Mechanically premix barium sulfate, sodium dodecylbenzene sulfonate and half of the lead powder, add dilute sulfuric acid after mixing, and stir for 20 minutes to obtain a premixed slurry;

[0050] A2: Heat the premixed slurry of A1 to 45°C, add all the remaining components except lead powder into the slurry, and stir for 1.5 hours to obtain a mixed slurry;

[0051] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0052] Example 3

[0053] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 16 parts of dilute sulfuric acid, 6 parts of water, 0.42 parts of elasticity-enhanced conductive filler, 0.30 parts of barium sulfate, 0.18 parts of surfactant, 0.14 parts of humic acid and 0.07 parts of sodium carboxymethyl cellulose.

[0054] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0055] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 40 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3.5 hours, refluxed in a 145°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0056] S2: According to parts by weight, the pre-oxidized carbon nanotubes prepared in S1 were added to 60 parts of N,N-dimethylformamide solvent, ultrasonically dispersed for 15 minutes, and then 0.4 parts of polyacryloyl chloride were added, stirred for 7 hours, filtered, washed, and dried to obtain pretreated carbon nanotubes, where polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0057] S3: adding the pretreated carbon nanotubes prepared in S2 to 6 parts of 1,4-dioxane by weight, ultrasonically dispersing for 10 minutes, adding 22 parts of hydroxyl-terminated polyurethane, adding 0.5 parts of triethylamine, and reacting for 8 hours to obtain carbon nanotube-modified polyurethane;

[0058] S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 4 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:105, and the length of the polyamide short fibers is 3 mm.

[0059] The surfactant is sodium dodecylbenzene sulfonate.

[0060] The density of the dilute sulfuric acid is 1.35 g / cm 3 .

[0061] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0062] A1: Mechanically premix barium sulfate, sodium dodecylbenzene sulfonate and half of the lead powder, add dilute sulfuric acid after mixing, and stir for 40 minutes to obtain a premixed slurry;

[0063] A2: Heat the premixed slurry of A1 to 55°C, add all the remaining components except lead powder into the slurry, and stir for 2.5 hours to obtain a mixed slurry;

[0064] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0065] Example 4

[0066] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 14.5 parts of dilute sulfuric acid, 4.5 parts of water, 0.39 parts of elasticity-enhanced conductive filler, 0.24 parts of barium sulfate, 0.13 parts of surfactant, 0.11 parts of humic acid and 0.055 parts of sodium carboxymethyl cellulose.

[0067] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0068] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 25 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 2.8 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0069] S2: According to parts by weight, the pre-oxidized carbon nanotubes prepared in S1 were added to 45 parts of N,N-dimethylformamide solvent, ultrasonically dispersed for 12 minutes, and then 0.25 parts of polyacryloyl chloride were added, stirred for 5.5 hours, filtered, washed, and dried to obtain pretreated carbon nanotubes, where polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0070] S3: According to parts by weight, the pretreated carbon nanotubes prepared in S2 were added to 4.5 parts of 1,4-dioxane, ultrasonically dispersed for 6 minutes, 19 parts of hydroxyl-terminated polyurethane were added, 0.35 parts of triethylamine were added, and the reaction was carried out for 5.5 hours to obtain carbon nanotube-modified polyurethane;

[0071] S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 2.5 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:98, and the length of the polyamide short fibers is 1.5 mm.

[0072] The surfactant is a mixture of sodium dodecylbenzene sulfonate and sodium lignin sulfonate, and the mass ratio of the two is 1:1.

[0073] The density of the dilute sulfuric acid is 1.28 g / cm 3 .

[0074] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0075] A1: Mechanically premix barium sulfate, surfactant and half amount of lead powder, add dilute sulfuric acid after mixing, and stir for 25 minutes to obtain a premixed slurry;

[0076] A2: Heat the premixed slurry of A1 to 48°C, add all the remaining components except lead powder into the slurry, and stir for 1.7 hours to obtain a mixed slurry;

[0077] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0078] Example 5

[0079] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 15.5 parts of dilute sulfuric acid, 5.5 parts of water, 0.41 parts of elasticity-enhanced conductive filler, 0.28 parts of barium sulfate, 0.17 parts of surfactant, 0.13 parts of humic acid and 0.65 parts of sodium carboxymethyl cellulose.

[0080] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0081] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 35 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3.2 hours, refluxed in a 142°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0082] S2: According to parts by weight, the pre-oxidized carbon nanotubes prepared in S1 were added to 55 parts of N,N-dimethylformamide solvent, ultrasonically dispersed for 14 minutes, and then 0.35 parts of polyacryloyl chloride were added, stirred for 6.5 hours, filtered, washed, and dried to obtain pretreated carbon nanotubes, where polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0083] S3: According to parts by weight, the pretreated carbon nanotubes prepared in S2 were added to 5.5 parts of 1,4-dioxane, ultrasonically dispersed for 8 minutes, 21 parts of hydroxyl-terminated polyurethane were added, 0.45 parts of triethylamine were added, and the reaction was carried out for 7.5 hours to obtain carbon nanotube-modified polyurethane;

[0084] S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 3.5 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:102, and the length of the polyamide short fibers is 2.5 mm.

[0085] The surfactant is sodium lignin sulfonate.

[0086] The density of the dilute sulfuric acid is 1.32 g / cm 3 .

[0087] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0088] A1: Mechanically premix barium sulfate, sodium lignin sulfonate and half of the lead powder, add dilute sulfuric acid after mixing, and stir for 35 minutes to obtain a premixed slurry;

[0089] A2: Heat the premixed slurry of A1 to 52°C, add all the remaining components except lead powder into the slurry, and stir for 2.3 hours to obtain a mixed slurry;

[0090] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0091] Comparative Example 1

[0092] The only difference from Example 1 is that in the preparation of the elasticity-enhanced conductive filler, the multi-walled carbon nanotubes are replaced by carbon black.

[0093] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0094] S1: According to the weight percentage, 1 part of carbon black is weighed and added to 30 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon black, wherein the mass fraction of concentrated sulfuric acid is 98%, and the mass fraction of concentrated nitric acid is 70%;

[0095] S2: According to parts by weight, the pre-oxidized carbon black prepared in S1 is added to 50 parts of N,N-dimethylformamide solvent, ultrasonically dispersed for 10 minutes, and then 0.3 parts of polyacryloyl chloride is added, stirred for 6 hours, filtered, washed, and dried to obtain pretreated carbon black, where polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0096] S3: According to parts by weight, the pretreated carbon black prepared in S2 was added to 5 parts of 1,4-dioxane, ultrasonically dispersed for 7 minutes, 20 parts of hydroxyl-terminated polyurethane was added, 0.4 parts of triethylamine was added, and the reaction was carried out for 6 hours to obtain carbon black modified polyurethane;

[0097] S4: Add polyamide short fibers to the carbon black modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 3 hours. The mass ratio of carbon black to polyamide short fibers is 1:100, and the length of the polyamide short fibers is 2 mm.

[0098] Comparative Example 2

[0099] The only difference from Example 1 is that no hydroxyl-terminated polyurethane is added in the preparation of the elasticity-enhanced conductive filler.

[0100] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0101] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 30 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0102] S2: adding the pre-oxidized carbon nanotubes prepared in S1 to 50 parts of N,N-dimethylformamide solvent, ultrasonically dispersing for 10 minutes, then adding 0.3 parts of polyacryloyl chloride, stirring for 6 hours, filtering, washing, and drying to obtain pretreated carbon nanotubes, wherein the polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0103] S3: adding the pretreated carbon nanotubes prepared in S2 to 5 parts of 1,4-dioxane by weight, ultrasonically dispersing for 7 minutes, adding 0.4 parts of triethylamine, and reacting for 6 hours to obtain modified carbon nanotubes;

[0104] S4: Add polyamide short fibers to the modified carbon nanotubes prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 3 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:100, and the length of the polyamide short fibers is 2 mm.

[0105] Comparative Example 3

[0106] The only difference from Example 1 is that in the preparation of the elasticity-enhanced conductive filler, the multi-walled carbon nanotubes are not pretreated.

[0107] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0108] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 30 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0109] S2: According to parts by weight, the pre-oxidized carbon nanotubes prepared in S1 were added to 5 parts of 1,4-dioxane, ultrasonically dispersed for 7 minutes, 20 parts of hydroxyl-terminated polyurethane were added, 0.4 parts of triethylamine were added, and the reaction was carried out for 6 hours to obtain carbon nanotube-modified polyurethane;

[0110] S3: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S2 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 3 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:100, and the length of the polyamide short fibers is 2 mm.

[0111] Comparative Example 4

[0112] The only difference from Example 1 is that, in the preparation of the elasticity-enhanced conductive filler, no hydroxyl-terminated polyurethane is added, and the multi-walled carbon nanotubes are not pretreated.

[0113] The preparation method of the elasticity-enhanced conductive filler comprises the following steps:

[0114] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 30 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0115] S2: adding the pretreated carbon nanotubes prepared in S1 to 5 parts of 1,4-dioxane by weight, ultrasonically dispersing for 7 minutes, adding 0.4 parts of triethylamine, and reacting for 6 hours to obtain modified carbon nanotubes;

[0116] S3: Add polyamide short fibers to the modified carbon nanotubes prepared in S2 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 3 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:100, and the length of the polyamide short fibers is 2 mm.

[0117] Comparative Example 5

[0118] The only difference from Example 1 is that the elasticity-reinforced conductive filler is replaced by carbon nanotube-modified polyurethane and polyamide short fibers, the carbon nanotube-modified polyurethane does not pre-coat the polyamide short fibers, and the two are added to the slurry as separate components.

[0119] A novel lead paste for negative plates of power batteries comprises the following components, measured by weight: 100 parts of lead powder, 15 parts of dilute sulfuric acid, 5 parts of water, 0.4 parts of polyamide staple fibers and carbon nanotube-modified polyurethane, 0.25 parts of barium sulfate, 0.16 parts of surfactants, 0.12 parts of humic acid and 0.06 parts of sodium carboxymethyl cellulose.

[0120] The mass ratio of the multi-walled carbon nanotubes to the polyamide short fibers is 1:100, and the length of the polyamide short fibers is 2 mm.

[0121] The preparation method of the carbon nanotube modified polyurethane comprises the following steps:

[0122] S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes was weighed, added to 30 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 3 hours, refluxed in a 135°C constant temperature oil bath, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid was 98%, and the mass fraction of concentrated nitric acid was 70%;

[0123] S2: adding the pre-oxidized carbon nanotubes prepared in S1 to 50 parts of N,N-dimethylformamide solvent, ultrasonically dispersing for 10 minutes, then adding 0.3 parts of polyacryloyl chloride, stirring for 6 hours, filtering, washing, and drying to obtain pretreated carbon nanotubes, wherein the polyacryloyl chloride is prepared by free radical polymerization of acryloyl chloride monomer;

[0124] S3: According to parts by weight, the pretreated carbon nanotubes prepared in S2 were added to 5 parts of 1,4-dioxane, ultrasonically dispersed for 7 minutes, 20 parts of terminal hydroxyl polyurethane were added, 0.4 parts of triethylamine were added, and the reaction was carried out for 6 hours to obtain carbon nanotube-modified polyurethane.

[0125] The surfactant is sodium lignin sulfonate.

[0126] The density of the dilute sulfuric acid is 1.30 g / cm 3 .

[0127] A novel method for preparing lead paste for negative plate of power battery comprises the following steps:

[0128] A1: Mechanically premix barium sulfate, sodium lignin sulfonate and half of the lead powder, add dilute sulfuric acid after mixing, and stir for 30 minutes to obtain a premixed slurry;

[0129] A2: Heat the premixed slurry of A1 to 50°C, add all the remaining components except lead powder into the slurry, and stir for 2 hours to obtain a mixed slurry;

[0130] A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.

[0131] Cycle life performance test of new power battery negative plate lead paste: Cycle life test at room temperature is carried out according to the test method required by GB / T22199.1-2017 "Valve-regulated Lead-acid Batteries for Electric Power Assisted Vehicles".

[0132] Cycle life / times Example 1 695 Example 2 682 Example 3 687 Example 4 696 Example 5 703 Comparative Example 1 440 Comparative Example 2 533 Comparative Example 3 598 Comparative Example 4 481 Comparative Example 5 572

[0133] The cycle life performance test results of the new power battery negative plate lead paste in Examples 1 to 5 show that the new power battery negative plate lead paste prepared by the preparation scheme of the present invention has a long service life and can be recycled for a long time.

[0134] The only difference between Comparative Example 1 and Example 1 is that in the preparation of the elasticity-enhanced conductive filler, the multi-walled carbon nanotubes are replaced by carbon black.

[0135] The cycle life of the new power battery negative electrode plate lead paste prepared in Example 1 is greater than the cycle life of the new power battery negative electrode plate lead paste prepared in Comparative Example 1, indicating that the addition of multi-walled carbon nanotubes can increase the cycle life of the power battery negative electrode plate lead paste.

[0136] The only difference between Comparative Example 2 and Example 1 is that no hydroxyl-terminated polyurethane is added in the preparation of the elasticity-enhanced conductive filler.

[0137] The cycle life of the new power battery negative plate lead paste prepared in Example 1 is greater than the cycle life of the new power battery negative plate lead paste prepared in Comparative Example 2, indicating that the addition of terminal hydroxyl polyurethane can improve the cycle life of the power battery negative plate lead paste.

[0138] The only difference between Comparative Example 3 and Example 1 is that, in the preparation of the elasticity-enhanced conductive filler, the multi-walled carbon nanotubes are not pretreated.

[0139] The cycle life of the new power battery negative electrode plate lead paste prepared in Example 1 is greater than the cycle life of the new power battery negative electrode plate lead paste prepared in Comparative Example 3, indicating that pretreating multi-walled carbon nanotubes during the preparation of elasticity-enhanced conductive fillers can enhance the effect of elasticity-enhanced conductive materials in the power battery negative electrode plate lead paste, thereby increasing the cycle life of the power battery negative electrode plate lead paste.

[0140] The only difference between Comparative Example 4 and Example 1 is that, in the preparation of the elasticity-enhanced conductive filler, no hydroxyl-terminated polyurethane is added, and the multi-walled carbon nanotubes are not pretreated.

[0141] The cycle life of the new power battery negative electrode lead paste prepared in Example 1 is greater than the cycle life of the new power battery negative electrode lead paste prepared in Comparative Example 4.

[0142] Comparative Example 4, in combination with Comparative Example 2 and Comparative Example 3, shows that the use of terminal hydroxyl polyurethane and the modification of multi-walled carbon nanotubes can synergistically promote the improvement of the cycle life of the negative plate lead paste of the power battery.

[0143] The only difference between Comparative Example 5 and Example 1 is that the elasticity-reinforced conductive filler is replaced by carbon nanotube-modified polyurethane and polyamide short fibers, the carbon nanotube-modified polyurethane does not pre-coat the polyamide short fibers, and the two are added to the slurry as separate components.

[0144] The cycle life of the new power battery negative plate lead paste prepared in Example 1 is greater than the cycle life of the new power battery negative plate lead paste prepared in Comparative Example 5, indicating that the pre-coating of polyamide staple fibers with carbon nanotube-modified polyurethane can enhance the effect of elastic reinforced conductive materials in the power battery negative plate lead paste, thereby improving the cycle life of the power battery negative plate lead paste.

[0145] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A new type of lead paste for negative plates of power batteries, comprising the following components, measured by weight: 100 parts of lead powder, 14 to 16 parts of dilute sulfuric acid, 4 to 6 parts of water, 0.38 to 0.42 parts of elasticity-enhanced conductive filler, 0.20 to 0.30 parts of barium sulfate, 0.12 to 0.18 parts of surfactant, 0.10 to 0.14 parts of humic acid and 0.05 to 0.07 parts of sodium carboxymethyl cellulose.

2. A novel lead paste for negative plate of power battery according to claim 1, characterized in that: The preparation method of the elasticity-enhanced conductive filler comprises the following steps: S1: According to the weight percentage, 1 part of multi-walled carbon nanotubes is weighed, added to 20-40 parts of concentrated sulfuric acid and concentrated nitric acid of the same mass as the concentrated sulfuric acid, stirred for 2.5-3.5 hours, refluxed in a constant temperature oil bath at 130-145°C, diluted, filtered, and dried to obtain pre-oxidized carbon nanotubes, wherein the mass fraction of concentrated sulfuric acid is 98%, and the mass fraction of concentrated nitric acid is 70%; S2: adding the pre-oxidized carbon nanotubes prepared in S1 to 40-60 parts of N,N-dimethylformamide solvent, ultrasonically dispersing for 10-15 minutes, then adding 0.2-0.4 parts of polyacryl chloride, stirring for 5-7 hours, filtering, washing, and drying to obtain pretreated carbon nanotubes; S3: adding the pretreated carbon nanotubes prepared in S2 to 4-6 parts of 1,4-dioxane by weight, ultrasonically dispersing for 5-10 minutes, adding 18-22 parts of hydroxyl-terminated polyurethane, adding 0.3-0.5 parts of triethylamine, and reacting for 5-8 hours to obtain carbon nanotube-modified polyurethane; S4: Add polyamide short fibers to the carbon nanotube-modified polyurethane prepared in S3 and stir evenly to obtain elastic reinforced conductive filler. The stirring time is 2 to 4 hours. The mass ratio of multi-walled carbon nanotubes to polyamide short fibers is 1:95 to 105, and the length of the polyamide short fibers is 1 to 3 mm.

3. A new type of lead paste for negative plate of power battery according to claim 2, characterized in that: The polyacryloyl chloride is prepared by free radical polymerization of polyacryloyl chloride monomer.

4. A novel lead paste for negative plate of power battery according to claim 1, characterized in that: The surfactant includes sodium dodecylbenzene sulfonate and / or sodium lignin sulfonate.

5. The novel lead paste for negative plate of power battery according to claim 1, characterized in that: The density of the dilute sulfuric acid is 1.25-1.35 g / cm 3 .

6. A method for preparing a new type of lead paste for negative electrode plates of a power battery as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: A1: Mechanically premix barium sulfate, surfactant and half amount of lead powder, add dilute sulfuric acid after mixing, and stir for 20-40 minutes to obtain a premixed slurry; A2: Heat the premixed slurry of A1 to 45-55°C, then add all the remaining components except lead powder, and stir for 1.5-2.5 hours to obtain a mixed slurry; A3: Add the remaining half of the lead powder into the mixed slurry of A2, mix well, and obtain the new power battery negative plate lead paste.